Estimation of nanoparticle concentration in tissue phantoms using diffused reflectance spectroscopy. - Lee, Chee Kiat. (2012)
Nanoparticle has been known to revolutionise our world and it is widely used in many biomedical applications such as Plasmonic Photothermal Therapy and many bio-imaging modalities. Along with the popularisation of nanoparticle in biomedical applications, it brought along issues of nanotoxicity and effectiveness which leads to the question of optimizing nanoparticle concentration. Currently, the only well established way of obtaining nanoparticle concentration is via Neutron Activation Analysis; a method which is very troublesome and destructive. On a similar note, some had tried to use other less invasive method such as Diffused Reflectance Spectroscopy, and used inverse algorithm based on diffusion theory to derive nanoparticle concentration.